RADI-21. IMAGING CHARACTERISTICS OF BRAF V600E MUTATED PEDIATRIC BRAIN TUMORS. Issue 2 (22nd June 2018) - Stence, Nicholas; Mulcahy-Levy, Jean; Hoffman, Lindsey; Green, Adam; Mirsky, David; Neuberger, Ilana; Fenton, Laura; Maloney, John; Kleinschmidt-DeMasters, Bette; Vibhakar, Rajeev; Foreman, Nicholas; Dorris, Kathleen
Abstract: INTRODUCTION: Genomic assessment of BRAF V600E has become routine in specific pediatric glioma subtypes in recent years given availability of targeted therapies. Comparison of imaging characteristics of pediatric gliomas with or without the V600E mutation has not been previously reported. METHODS: Pathology reports of pediatric brain tumors diagnosed from 2010-2017 at a single institution were searched for keywords "V600E" or "VE1" using institutional databases (Nuance mPower, Nuance Communications). Cases where V600E testing was successfully performed and whose pathologic diagnosis was ganglioglioma, pleomorphic xanthoastrocytoma (PXA) or epithelioid glioblastoma were included. Preoperative MRI studies were reviewed by a single neuroradiologist (NVS) for tumor volume, T1 and T2 signal characteristics, cystic or solid components, enhancement, adjacent non-enhancing T2 hyperintensity, hemorrhage, DWI signal and ADC values in solid components, and location. Review of charts and follow-up imaging studies was conducted to evaluate tumor recurrence or progression. Fisher's exact test was used for categorical data and a two-tailed unpaired t-test was used for continuous data. RESULTS: 30 tumors met pathologic inclusion criteria, including 18 gangliogliomas, 10 PXAs and 2 epithelioid glioblastomas. Average age was 10.6 years (range 0.64-24 years). IHC or molecular analysis identified BRAF V600E in 16 tumors. These tumors were significantly more likely to exhibit hyperintensity on DWI (p=0.009), lower ADC values (p=0.046), and non-enhancing T2 hyperintensity adjacent to solid enhancing components. CONCLUSIONS: BRAF V600E mutant tumors demonstrate restricted diffusion, which may indicate differences in cellularity or tumor microarchitecture. Further study with advanced imaging sequences, including MR spectroscopy and perfusion, is needed.